A Rare Case of Amoebic Meningoencephalitis - Dr. Shaik Md Shoaib; Dr. Uma M Anand Kumar; Dr Manzoor Sharieff, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Free-living amebas are protozoan environmental parasites, mainly in freshwater, lakes, and rivers, without needing a definitive host.1 In humans, there are four main genera of amebas that can cause disease, namely Naegleria (only Naegleria fowleri), Acanthamoeba (several species). A 32 years old male came with complaints of fever, altered sensorium, vomitings for 1 day and presented with involuntary movements of all four limbs.On presentation Blood pressure was 160/100 mm of Hg , pulse rate- 107 bpm, RR-36 cpm and was intubated in view of low GCS. The patient was initiated on intravenous Amphitericin B and dose was determined using body weight, and was changed to tab fluconazole and tab azithromycin in view of acute kidney injury after 9 days of administration. Patient survived with residual neurological deficits.